A Multilevel Analysis of the Relation Between Bullying Roles and Social and Emotional Competencies - Coelho, Vítor Alexandre (Journal of interpersonal violence, 2021)
This study investigated how social and emotional competencies are related to middle school students’ involvement in bullying, and whether class-levels variables influence this association. There were 668 participants (Mage = 12.73, SD = 1.08) who participated in a screening for inclusion in a social and emotional learning program. Results showed that students not involved in bullying displayed higher levels of self-esteem than students involved in bullying in any role (victims, perpetrators, or bully-victims), higher levels of self-control and social awareness than perpetrators and bully-victims, and higher levels of responsible decision making than bully-victims. Gender did not moderate the relation between any bullying roles and social and emotional competencies, but class size moderated the relation between being a bully/victim and self-esteem and between being a bully and self-control. These results supported the relevance of including class-level variables when analyzing the relation between bullying and social and emotional competencies.